2010
DOI: 10.1007/s10439-010-9899-3
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Platforms for Studies of Angiogenesis, Cell Migration, and Cell–Cell Interactions

Abstract: Recent advances in microfluidic technologies have opened the door for creating more realistic in vitro cell culture methods that replicate many aspects of the true in vivo microenvironment. These new designs (i) provide enormous flexibility in controlling the critical biochemical and biomechanical factors that influence cell behavior, (ii) allow for the introduction of multiple cell types in a single system, (iii) provide for the establishment of biochemical gradients in two- or three-dimensional geometries, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 96 publications
(114 reference statements)
0
132
0
Order By: Relevance
“…Microfluidic technology has several advantages over conventional methods in terms of precise control of microenvironmental factors, and high-resolution imaging of cell motility or cell-to-cell interactions. 12,13 Several studies have utilized microfluidic technology to model different stages of the cancer metastasis. Kim et al have reported a cancer angiogenesis model by attaching endothelial cells on the sidewall of fibrin gel, and stimulating them by co-culturing with spatially separated cancer cells.…”
Section: B)mentioning
confidence: 99%
“…Microfluidic technology has several advantages over conventional methods in terms of precise control of microenvironmental factors, and high-resolution imaging of cell motility or cell-to-cell interactions. 12,13 Several studies have utilized microfluidic technology to model different stages of the cancer metastasis. Kim et al have reported a cancer angiogenesis model by attaching endothelial cells on the sidewall of fibrin gel, and stimulating them by co-culturing with spatially separated cancer cells.…”
Section: B)mentioning
confidence: 99%
“…Recently, cell migration on gradient materials [9] and their potential applications in tissue regeneration [10,11] have attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For example, endothelial cells (ECs) have been seeded in fabricated microchannels on both nonbiological 9,10 substrates or within biological substrates 11,12 to mimic vessels; however, while this approach offers some insight into the effects of convective forces on cells, the channels are not living vessels and thus are unresponsive to the dynamic metabolic demands of the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%